The Petrine instauration : religion, esotericism and science at the court of Peter the Great, 1689-1725 - Collis, Robert. (Aries Book Series, 2012)
The reign of Peter the Great (1672-1725) was marked by an unprecedented wave of reform in Russia. This book provides an innovative reappraisal of the Petrine Age, in which hitherto neglected aspects of the tsar's transformation of his country are studied. More specifically, the reforms enacted by the tsar are assessed in light of the religious notion of instauration - a belief in the restoration of Adamic knowledge in the last age - and a historical and cultural analysis of the impact of Western esotericism at the Russian court. This book will appeal to scholars of Russian history and religion, as well as being of wider interest to those studying Western esotericism in Early Modern and eighteenth-century Europe.